2010
DOI: 10.1073/pnas.0913002107
|View full text |Cite
|
Sign up to set email alerts
|

Percolative theories of strongly disordered ceramic high-temperature superconductors

Abstract: Optimally doped ceramic superconductors (cuprates, pnictides, etc.) exhibit transition temperatures T c much larger than strongly coupled metallic superconductors like Pb (T c ¼ 7.2 K, E g ∕kT c ¼ 4.5) and exhibit many universal features that appear to contradict the Bardeen, Cooper, and Schrieffer theory of superconductivity based on attractive electron-phonon pairing interactions. These complex materials are strongly disordered and contain several competing nanophases that cannot be described effectively by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Our quantitative results should be tested against theories of composite, granular superconductors proposed for cuprates (10,14,15,25,(30)(31)(32)(55)(56)(57)(58)(59)(60)(61)(62). The X-ray data indicate that these theories must take into account not only the usual superconducting proximity effects, but also the effects of the strains the two components exert on each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our quantitative results should be tested against theories of composite, granular superconductors proposed for cuprates (10,14,15,25,(30)(31)(32)(55)(56)(57)(58)(59)(60)(61)(62). The X-ray data indicate that these theories must take into account not only the usual superconducting proximity effects, but also the effects of the strains the two components exert on each other.…”
Section: Discussionmentioning
confidence: 99%
“…1. The lattice complexity of superconducting copper oxides was neglected by most popular theories of high T c superconductivity, while percolative theories for granular superconductors were invoked because of the relevance of lattice disorder for electronic properties (10).…”
mentioning
confidence: 99%
“…For instance, the limit of stability for tetrahedral units in SiO 2 or GeO 2 glass corresponds to the packing fraction found for an RLP of hard spheres, with the majority of datasets pointing to a maximum packing fraction that is comparable to the RCP limit (24)(25)(26)(27). This structural map (34)(35)(36), in which n O A is classified in terms of η O , allows for several properties of disordered oxides to be rationalized, and leads to predictive power for estimating the likely regimes of topological change.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there is overwhelming evidence of domain pattern formation for an array of emergent phenomena, including metal-insulator transitions [7][8][9][10][11], charge/magnetic ordering [12][13][14], and unconventional superconductivity [15][16][17]. Several studies have identified these spatial textures as essential underpinnings for novel phenomena in TMOs and other correlated electron [5,13,[18][19][20][21].Rare earth nickelates (RENiO 3 ) are a fertile platform to realize and explore the emergent physics brewing in proximity to electronic symmetry-breaking phenomena, thanks to the cooperative action of the coupled charge, spin, and lattice degrees of freedom. In this family of compounds, the dominant structural/electronic instability sets the stage for a first-order transition (P2 1 /n to Pbnm) to a bond-disproportionated phase, that is accompanied by a concurrent insulator-to-metal transition (IMT).…”
mentioning
confidence: 99%